2021
DOI: 10.4085/1062-6050-282-21
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Analysis of Forces Applied by Trained Clinicians During 2-Handed Instrument-Assisted Soft Tissue Mobilization

Abstract: Instrument-assisted soft tissue mobilization (IASTM) is a common intervention among clinicians. Despite the popularity, little is known about the forces applied by the clinician with the instruments during treatment. The purpose of this investigation was to examine the forces applied by trained clinicians using IASTM instruments during a simulated treatment. Eleven IASTM trained (Graston Technique, Técnica Gavilán, or RockBlades) clinicians (Physical Therapist = 2, Chiropractor = 2, Athletic Trainer = 7) parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Additionally, there is evidence for intraclinician reliability of applied IASTM forces for one-handed IASTM grips with the TG, FAT and RB 14. While IASTM force reliability data for a two-handed grip was not identified in the literature, two-handed force data from a simulated treatment on a force plate was found: IASTM forces ranged from 1.1 to 21.3 N for average peak force and 0.9 to 15.3 N for average mean force across clinicians using the EM, RB, FAT, TG and GT instruments 15. The variations in the range of forces reported by these studies across the aforementioned instruments requires further investigation into whether grip or instrument influenced force application.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, there is evidence for intraclinician reliability of applied IASTM forces for one-handed IASTM grips with the TG, FAT and RB 14. While IASTM force reliability data for a two-handed grip was not identified in the literature, two-handed force data from a simulated treatment on a force plate was found: IASTM forces ranged from 1.1 to 21.3 N for average peak force and 0.9 to 15.3 N for average mean force across clinicians using the EM, RB, FAT, TG and GT instruments 15. The variations in the range of forces reported by these studies across the aforementioned instruments requires further investigation into whether grip or instrument influenced force application.…”
Section: Introductionmentioning
confidence: 95%
“…The recent studies13–15 on clinician applied IASTM forces during simulated treatment scenarios did not examine if IASTM forces vary across different IASTM instruments or whether one-handed or two-handed grips influence force application. The potential for force variation across IASTM instruments and one-handed or two-handed stroke type would be valuable for informing clinical practice, literature interpretation and future research.…”
Section: Introductionmentioning
confidence: 99%
“…One notable therapeutic approach is instrumentassisted soft tissue mobilization (IASTM) . This technique involves the use of instruments to manipulate soft tissues (Jo et al, 2023), breaking up scar tissue, mobilizing muscles (Stevenson et al, 2023) and enhance healing processes (Croft et al, 2022). Studies have demonstrated the effectiveness of IASTM in reducing spasticity (Bar-On et al, 2015) and improving upper extremity function in stroke rehabilitation (Shruti Deshpande et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature provides valuable insights into various therapeutic interventions and approaches for individuals with cerebral palsy (Orhan et al, 2018) and other musculoskeletal disorders Das et al, 2022;Singh and Sharma, 2023;Khant et al, 2023;Stevenson et al, 2023;Liu and Wang, 2023). These interventions range from Astym therapy, taskoriented training, acupuncture and IASTM to surgical interventions, collectively contributing to understanding effective strategies for enhancing motor function, reducing spasticity and improving overall functional ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation